2010
DOI: 10.1103/physrevlett.104.018701
|View full text |Cite
|
Sign up to set email alerts
|

Towards Design Principles for Optimal Transport Networks

Abstract: We investigate the navigation problem in lattices with long-range connections and subject to a cost constraint. Our network is built from a regular two-dimensional (d=2) square lattice to be improved by adding long-range connections (shortcuts) with probability P(ij) approximately r(ij)(-alpha), where r(ij) is the Manhattan distance between sites i and j, and alpha is a variable exponent. We introduce a cost constraint on the total length of the additional links and find optimal transport in the system for alp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
147
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(153 citation statements)
references
References 21 publications
6
147
0
Order By: Relevance
“…The allocation procedure is finished when the pool of available cities is exhausted. We must note that a comparison with a socially optimal network (Li et al 2010) is also useful here; further work is needed to establish norms for optimality and generate a meaningful optimum.…”
Section: Population Distribution Network Speeds and Network Ownershipmentioning
confidence: 99%
See 2 more Smart Citations
“…The allocation procedure is finished when the pool of available cities is exhausted. We must note that a comparison with a socially optimal network (Li et al 2010) is also useful here; further work is needed to establish norms for optimality and generate a meaningful optimum.…”
Section: Population Distribution Network Speeds and Network Ownershipmentioning
confidence: 99%
“…This is presumably because of limited data availability, computational limitations and difficulties in reproducing topologically realistic links or 'shortcuts' (Li et al 2010). The aim of this paper is to introduce transport link scanner (TLS), an agent-based model that simulates the overall geographic diffusion of a transport network through the individual investment decisions that drive network expansion, and to demonstrate that it is able to reproduce a historical network expansion process reasonably accurate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the design and development of optimal navigation can be achieved exploiting shortest paths, either with local knowledge and the presence of long-range connections in a lattice network (25) or by imposing cost constraints, regardless of the available (global or local) information (26). However, in the presence of random failures it is not possible to have real-time information about the subsequent congestion.…”
mentioning
confidence: 99%
“…In recent years, several public transport systems (PTS) have been investigated using various concepts of the statistical physics of complex networks [10][11][12][13][14][15][16][17][18][19][20]. Among them, many studies have focused on the complexity of urban public transport systems.…”
mentioning
confidence: 99%